2020
DOI: 10.1177/1945892420920505
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Balloon Sinuplasty Adverse Events With the Innovative OpenFDA Database

Abstract: Background Balloon sinuplasty (BSP) has become a common, minimally invasive treatment for chronic sinusitis. Like any surgical procedure, there are definite risks when using it as a stand-alone procedure or in conjunction with other revision procedures. Objective To explore the adverse events of BSP using the openFDA cloud with regard to malfunction and injury following surgery. Methods Between January 2015 and December 2018, the Food and Drug Administration’s (FDA) openFDA database was queried for adverse eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…11 Several large database studies have recently investigated the rates of BSD-related complications and have identified that BSD of the frontal sinus is particularly prone to increased risk of complications. 4,12,13 In the largest database study to date investigating BSD complications, Chaaban et al 13 identified a complication rate of 0.35% for skull base complications, 2.95% for orbital complications, and 2.03% for bleeding complications of 2851 total procedures studied. Another database study identified a total of 102 patient-related complications reported to the FDA between 2008 and 2018.…”
Section: Discussionmentioning
confidence: 99%
“…11 Several large database studies have recently investigated the rates of BSD-related complications and have identified that BSD of the frontal sinus is particularly prone to increased risk of complications. 4,12,13 In the largest database study to date investigating BSD complications, Chaaban et al 13 identified a complication rate of 0.35% for skull base complications, 2.95% for orbital complications, and 2.03% for bleeding complications of 2851 total procedures studied. Another database study identified a total of 102 patient-related complications reported to the FDA between 2008 and 2018.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent meta-analyses and systematic reviews, more evaluations are needed to demonstrate its clinical usefulness in terms of improving the quality of life and the comparative efficacy of BCD compared to standard treatment regimens in specific patients' subgroups such as children (61,(65)(66)(67). Moreover, as with all interventions, BCD, although minimally invasive, can be associated with adverse events such as cerebrospinal fluid leaks, mainly reported with frontal sinus procedures (62).…”
Section: Balloon Catheter Dilatationmentioning
confidence: 99%
“…BCD is a minimally invasive procedure aimed to restore physiological sinus drainage, safely dilating sinuses through microfractures ( 61 ). BCD has become a common treatment for chronic sinusitis in the United States ( 62 ). It is among the most common office-based rhinological procedures ( 60 ).…”
Section: Technological Innovationmentioning
confidence: 99%
“…In 2014, the US Food and Drug Administration (FDA) launched openFDA, an open‐source database that provides access to publicly available medical device reports, enforcement reports, and drug event reports (https://open.fda.gov/about/). The database has been used to explore complications related to tonsillectomy, balloon sinuplasty, nasopharyngoscopy, posterior nasal nerve cryoablation, and dermal filler injection 14–19 . Using openFDA, we sought to investigate and characterize adverse events related to microdebrider use and device malfunction in sinus surgery.…”
Section: Introductionmentioning
confidence: 99%